T Cell–Expressed CD40L Potentiates the Bone Anabolic Activity of Intermittent PTH Treatment. (April 2015) - Robinson, Jerid W; Li, Jau‐Yi; Walker, Lindsey D; Tyagi, Abdul Malik; Reott, Michael A; Yu, Mingcan; Adams, Jonathan; Weitzmann, M Neale; Pacifici, Roberto
ABSTRACT: T cells are known to potentiate the bone anabolic activity of intermittent parathyroid hormone (iPTH) treatment. One of the involved mechanisms is increased T cell secretion of Wnt10b, a potent osteogenic Wnt ligand that activates Wnt signaling in stromal cells (SCs). However, additional mechanisms might play a role, including direct interactions between surface receptors expressed by T cells and SCs. Here we show that iPTH failed to promote SC proliferation and differentiation into osteoblasts (OBs) and activate Wnt signaling in SCs of mice with a global or T cell–specific deletion of the T cell costimulatory molecule CD40 ligand (CD40L). Attesting to the relevance of T cell–expressed CD40L, iPTH induced a blunted increase in bone formation and failed to increase trabecular bone volume in CD40L –/– mice and mice with a T cell–specific deletion of CD40L. CD40L null mice exhibited a blunted increase in T cell production of Wnt10b and abrogated CD40 signaling in SCs in response to iPTH treatment. Therefore, expression of the T cell surface receptor CD40L enables iPTH to exert its bone anabolic activity by activating CD40 signaling in SCs and maximally stimulating T cell production of Wnt10b. © 2014 American Society for Bone and Mineral Research.